2022
DOI: 10.1177/00469580221126295
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Evidence-based Intervention Criteria in U.S. Federal Grant Funding Announcements for Behavioral Healthcare

Abstract: Recent U.S. federal government policy has required or recommended the use of evidence-based interventions (EBIs), so that it is important to determine the extent to which this priority is reflected in actual federal solicitations for intervention funding, particularly for behavioral healthcare interventions. Understanding how well such policies are incorporated in federal opportunity announcements (FOAs) for grant funding could improve compliance with policy and increase the societal use of evidence-based inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Service providers in the behavioral health disciplines are increasingly expected to use evidence-based interventions in their treatment of various behavioral health problems. 1 - 4 Evidence-based interventions are interventions that have “demonstrated positive outcomes through high quality clinical or organizational research” (p.1). 5 One type of publicly available resource for locating information about evidence-based interventions is the evidence-based program resources website (EBPR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Service providers in the behavioral health disciplines are increasingly expected to use evidence-based interventions in their treatment of various behavioral health problems. 1 - 4 Evidence-based interventions are interventions that have “demonstrated positive outcomes through high quality clinical or organizational research” (p.1). 5 One type of publicly available resource for locating information about evidence-based interventions is the evidence-based program resources website (EBPR).…”
Section: Introductionmentioning
confidence: 99%
“…Definitions of what constitute an evidence-based intervention vary depending on who or what agency defines them. 3 , 10 , 11 Likewise, variations in the criteria used by EBPRs to construct those rating categories are examined in several studies. For example, the Pew-MacArthur Charitable Trusts (PEW) found that specific details about the way different EBPRs construct their rating categories make it difficult to compare the ratings given to the same interventions.…”
Section: Introductionmentioning
confidence: 99%